Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1366866716 species occurrences available in GBIF matching the query: { "Year" : [ "1000-2018" ] } The dataset includes 1366866716 records from 29168 constituent datasets: 961 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 241 records from Amphibian Specimens of the Yamagata Prefectural Museum. 4 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 592424 records from Plant. 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from A taxonomic review of the genus Asterostegus (Echinodermata: Ophiuroidea), with the description of a new species. 4 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 108 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 22 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 395 records from Nannofossil abundance of Hole 37-334. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 15 records from Contributions to the knowledge of Dichelops (Dichelops) with the description of a new species (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 59 records from Schulgelände SGD/Viersen. 2 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 12684 records from Colecção Entomológica IIA. 1290 records from Flora genérica de las gramíneas del estado de Tlaxcala. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 1 records from Zur Kenntnis der Lithobiiden. 16995 records from MZFC/Coleccion de Aves. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 307 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 7339 records from Natural History Museum Maastricht (NL) - Herbarium. 7144 records from DMNS Egg Collection (Arctos). 8859 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 1300 records from Crustacean specimens of Bihoro Museum. 361 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 59 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 13 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 371 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 22 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 1702 records from BioGIS - Bryophytes - HUJ collections. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 87 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 7 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 745 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 2 records from The Chinese Folsomia with a description of a new species (Collembola: Isotomidae). 757 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 2 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 51 records from Coccoliths in sediment core GIK23065-3. 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Neotropical Monogenoidea. 60. Two new species of Gyrodactylus (Monogenoidea: Gyrodactylidae) from the armored-catfish, Pareiorhaphis parmula Pereira (Loricariidae) and from the cascarudo, Callichthys callichthys (Linnaeus) (Callichthyidae) from Brazil. 121 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 9 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 16 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 1 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 232 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 7 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 9 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 15 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 26159 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 17 records from Analyses of the recent components of sediment core PS1219-1. 42696 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 353 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 11 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 120 records from BIRDRACE The early birds. 6 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 2132 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 186099 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 9 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 44 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 1 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 20838 records from Birds Specimens. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 86 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 6979 records from Upper Silesian Museum, Bird Observations. 53 records from Planktic foraminifera abundance of Hole 23-227. 145 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 20093 records from DMNS Mammal Collection (Arctos). 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 235 records from SEWBReC Springtails and allies (South East Wales). 2 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 64 records from Bats of northeastern Vietnam. 1052 records from IBF Monitoring of Fungi. 261 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 96442 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 6 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 1184 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 6479 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 35 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 975644 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 9 records from Planktic foraminifera abundance of Hole 14-144. 413272 records from DATAVES. 2572 records from seawater metagenome Metagenome. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 530 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3806 records from Heliconiine Butterfly Collection Records from University of Cambridge. 1 records from Redescription of Leptogyra bujnitzkii (Gorbunov, 1946) comb. nov., the first representative of the gastropod subclass Neomphaliones from the high Arctic. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from Planktic foraminifera abundance of Hole 53-418B. 122 records from Colección de Líquenes Austroamericanos Ex Herbario Regnelliano- FML. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 1993 records from Berea College, Ralph L. Thompson Herbarium. 409 records from Distribution of nanoplankton at trap WR2. 38 records from Taxonomic studies on Dolichothrips (Thysanoptera: Phlaeothripinae), pollinators of Macaranga trees in Southeast Asia (Euphorbiaceae). 79 records from Birdrace-Bielefinken-Bielefeld. 7443 records from Fish specimens of Toyama Science Museum. 121 records from Range table from ostracoda in ODP Hole 143-866B. 642 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 1 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 5999 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 140788 records from Fermanagh Flora. 8624 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 178702 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 1110 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 78 records from Données de la naturaliste Anna Even. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 10 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 2 records from A new species of Platyauchenia Stürm, 1843 (Coleoptera: Chrysomelidae: Cassidinae) from Brazil. 26583 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 10 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 95 records from Kystfuruskoger i Tysnes og Fusa. 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Discovered online: Hibiscus hareyae sp. nov. of sect. Lilibiscus (Malvaceae), threatened in coastal thicket at Lindi, Tanzania. 13 records from Planktic foraminifera abundance of Hole 19-185. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 14 records from The genus Calodera Mannerheim in Canada (Insecta, Coleoptera, Staphylinidae, Aleocharinae). 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 1 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 6191 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 19 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 15 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 53 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 6 records from A Catalogue and Historical Study of the Odonata of Ecuador. 371 records from Bannwald Burghauser Forst. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 192 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 6 records from A review of the subfamily Anobinae with the description of a new species of Baniana Walker from North and Central America (Lepidoptera, Erebidae, Anobinae). 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 4 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 14 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 186 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 9 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 10517 records from Bryophyte specimens of The Nagoya University Museum. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 29365 records from University of Guam Insect Collection. 532 records from Plant species from the sacred and community forests of Mono departement. 4 records from Morphology of pupae of the Pyropteron (Synansphecia) triannuliforme-group (Lepidoptera: Sesiidae). 480819 records from KTP Ring Data. 44 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 298 records from Planktic foraminifera abundance of Hole 32-310. 567 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 4 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 8 records from Report on a collection of dragonflies (Odonata) from the Andaman Islands.. 10 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 2 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 23 records from Morphologische Daten von Natrix. 2 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 4 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 1 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 18 records from Collection botanique Lamy de la Chapelle E. (BOUM). 7552 records from Brown University Herbarium. 1056 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 90 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19339 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 5184 records from MCP-Aves - Coleção de Aves. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 52 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 46 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 135 records from Nannofossil abundance of Hole 36-329. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 728 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 821 records from Bird specimens of Saitama Museum of Natural History. 382 records from orthopteracollections-nhmj-ioj. 2 records from Carnivores of Syria. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 1 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 5 records from Redescription of the types of species of Anastatus Motschulsky, 1859 (Hymenoptera: Chalcidoidea: Eupelmidae) described by J. K. Sheng and coauthors. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 8949 records from Collections of Bioclass, school #179, Moscow. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 18 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 13179 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 4 records from Dinoflagellate abundance of Hole 14-144. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 8 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 18 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 301406 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 49 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 7 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 5 records from Contributions to the knowledge of Atlantic Canadian Histeridae (Coleoptera). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 5 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 10776 records from CEFS_16S_ITS. 1 records from The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae). 1 records from Henanocerus lineatus gen. nov. and sp. nov., a new leafhopper feeding on Populus tomentosa Carrière from China (Hemiptera, Cicadellidae). 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 11 records from Inventaire et regroupement de données Natura 2000. 1272 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 68 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 21 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 127 records from Planktic foraminifera abundance of Hole 37-332. 521 records from Schanzenanlage Bergham. 1 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1157 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 14 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 6368 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 18 records from Naturtag. 20619 records from Herbier Louis-Marie (QFA) - Collection de lichens. 134 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 79 records from Diatom abundance of Hole 95-613. 1943 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 78 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 28075 records from Lepidoptera specimen database of Japan. 4 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 273 records from Planktic foraminifera abundance of Hole 68-503B. 130 records from BIRDRACE - The famous Grouse feat. The James. 6 records from Synopsis of the genus Termitozophilus Silvestri (Coleoptera, Staphylinidae, Aleocharinae, Corotocini). 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 40510 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 2729301 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 22 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 4617 records from Inventaire de la flore du Grand Poitiers 2009. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1513 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 49118 records from Naturalis Biodiversity Center (NL) - Diptera. 37 records from FBIP: scallop population genetics. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 22 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 14 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 8 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 137 records from Colección Ficológica del Herbario Criptogámico de la FML. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 352 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 81329 records from natagora-earlybirds. 9143 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 16 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 13 records from Reptiles Specimens of Akita Prefectural Museum. 96 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 205 records from UWIZM Snakes. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 26389 records from Protist Diversity in the East China Sea. 120 records from Données espèces - Expertise IPE 79. 1705882 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 50 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 20 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 728 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 6 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1900 records from Fungi Collection. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1 records from Species status of Colias misti (Pieridae: Coliadinae) from the Arequipa region South Peru, and a description of its new subspecies, from Cotahuasi canyon South-Central Peru. 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 4102 records from California State University, Long Beach Birds. 87 records from Données espèces - Expertise IPE 70. 1028 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 18 records from Thirteen new records of ferns from Brazil. 575 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 130763 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 132 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 32694 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 152 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 89474 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 23 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 6279 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 47 records from Schulgelände (Wetter). 282 records from Deponie Klausdorf. 31 records from The Brazilian Goblin Spiders Of The New Genus Predatoroonops (Araneae: Oonopidae). 5 records from First record and new species of the genus Calambus Thomson (Coleoptera Elateridae, Dendrometrinae) from Taiwan. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 1 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 6186 records from NE Scotland fish records 1800-2010. 259 records from Natura 2000 Parc naturel régional de Lorraine. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 50 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 261 records from bmhs_weatherheadshell_collection. 57919 records from Fichier communal des ongulés. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 18 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 21 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 1 records from A new species of the genus Haplotropis Saussure, 1888 (Orthoptera, Acridoidea, Pamphagidae) from Inner Mongolia, China. 6 records from Two new species and two newly recorded species of the subgenus Empoasca Walsh from Korea (Hemiptera: Cicadellidae: Typhlocybinae). 3891 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 42 records from Living Cirripedia. 2 records from A contribution to the knowledge of the genera Fissocantharis Pic, 1921 and Micropodabrus Pic, 1920 from Taiwan (Coleoptera, Cantharidae). 9 records from New species of palaearctic Euphthiracaridae (Acari, Oribatida). 2070 records from Helmintos parásitos de peces del sureste de México. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from A new pseudoscorpion genus from western Georgia (Pseudoscorpiones: Neobisiidae: Cornuroncus n. gen.), with a key to all Neobisiinae genera. 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 80 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3753 records from Données naturalistes de Charlotte PICARD. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 4 records from Ostracoda abundance of Hole 44-390. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 11065 records from University of Nebraska State Museum Birds Collection. 115 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 8 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 21882 records from University of California Santa Barbara Invertebrate Zoology Collection. 356 records from Données naturalistes de Hubert GUIMIER. 1807 records from Données de la collection Rousset -1947-2013. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 143 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 2 records from A new species of planthopper in the genus Myxia (Hemiptera: Auchenorrhyncha Cixiidae) from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 90 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 6078 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 2 records from A new mayfly Thraulus species (Ephemeroptera: Leptophlebiidae) from Peninsular India. 12094 records from Amino acid addition experiment Metagenome. 7 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 140 records from Hartland Nature Club Lepidoptera Collection. 116177 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 26 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanteriidae).. 113782 records from Fish specimens of Kagoshima University Museum. 42027 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 13657 records from UTEP Invertebrates (Arctos). 3777 records from Diptera Collection of Museum and Institute of Zoology PAS. 9 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 17 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 3 records from The genus Aivalykus Nixon, 1938 (Hymenoptera: Braconidae: Doryctinae) with description of a new species from India and Arabian Peninsula. 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1482 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3109 records from Insectes Hyménoptères Scollidés de France. 3621 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 2 records from Description of a new brachypterous scarab species, Orphnus brevialatus (Coleoptera: Scarabaeidae: Orphninae) from East Africa, with notes on flightlessness in the orphnines. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 18 records from Revision of the Metallactus generosus species-group with a preliminary evaluation of the effectiveness of the endophallus morphology in distinguishing critical sibling species (Coleoptera: Chrysomelidae: Cryptocephalinae). 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 26 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 1 records from Redescription of larva of the South African endemic dobsonfly genus Chloroniella Esben-Petersen, 1924 (Megaloptera, Corydalidae), with a proposed terminology for Corydalidae larval sclerites. 916 records from IOW Natural History & Archaeological Society Marine Records. 15 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 6190 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 314 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 25 records from Contribution to the knowledge of the genus Cordilura Fallén (Diptera, Scathophagidae) from Japan, with descriptions of three new species. 8 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 245 records from Planktic foraminifera counts of sediment core V14-77. 135 records from Waldi-Weiher. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 19 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 35 records from Données de NICOLAS Vincent (SAPROX). 16844 records from Données Entomologiques A. HORELLOU 1988-2018. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 30042 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 321 records from Foraminifera abundance of Hole 74-526A. 55 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1491 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 21 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 23 records from Benthic foraminifera abundance of Hole 42-379A. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 60 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 903 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2508 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 232 records from Planktic foraminifera abundance of Hole 21-207. 634139 records from Flora Atlas N.T.. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 82 records from Herbario COFC de la Universidad de Córdoba: colección histórica. 7 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 11024 records from WOLL AVH data. 2 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 10 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 50 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3638 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 24 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 8 records from A new species of Phonotimpus Gertsch & Davis, 1940 (Araneae: Phrurolithidae) from Mexico. 2718 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 139 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 93 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 186 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 10 records from Ostracoda abundance of Hole 32-306. 1169 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 2 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 244 records from Nannofossil abundance of Hole 29-281. 26 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 580 records from Rare plants database extract from Scottish Natural Heritage. 11 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 194 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 2497 records from Données des collections d'algues du MNHN. 16090 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 302 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 1 records from Redefinition of Cornexcisia Fan & Kano, 2000 (Diptera: Sarcophagidae), with the first description of the female of Sarcophaga kurahashii (Shinonaga & Tumrasvin, 1979). 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 422150 records from NOAA AFSC North Pacific Groundfish Observer. 27160 records from Formidabel; Belgian Ants Database. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 7 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 32 records from Revision of the genus Neozavrelia Goetghebuer, Thienemann, 1941 (Diptera Chironomidae) from Eastern Siberia and the Russian Far East, with the description of new species. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 22 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 3 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 2 records from Eubostrichopsis johnpearsei n. gen., n. sp., the first stilbonematid nematode (Nematoda, Desmodoridae) from the US West Coast. 16 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 587 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 2 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 204205 records from University of Michigan Museum of Zoology, Division of Birds. 39 records from Planktic foraminifera abundance of Hole 14-137. 5 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 2585 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 752 records from Données naturalistes de Monsieur JOURDE Rémi. 243 records from Données naturalistes de AUNEAU Florent. 2203 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 494 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 7 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 19 records from Taxonomic revision of the Afrotropical scarab beetle genus Cerhomalus Quedenfeldt, 1884 (Coleoptera: Scarabaeidae: Orphninae). 2 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 37 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 2 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 24 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 3 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 134 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 62 records from Zoo Frankfurt. 212 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 41 records from An Integrative Approach to the Taxonomy of Oenopiella Bergroth (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) with the Description of Two New Species from Argentina and Southern Brazil. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1085627 records from Fungal Records Database of Britain and Ireland. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from A new genus of Podoscirtini with one new species from Guangxi, China (Orthoptera: Gryllidae; Podoscirtinae). 31 records from Bulletin d'informations de l'Association française de Lichénologie. 38 records from Nannofossil abundance of Hole 10-89. 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 142 records from A Revision of the Nearctic Predaceous Midges in the Bezzia (Bezzia) pulverea complex (Diptera: Ceratopogonidae). 752 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61068 records from La familia Asteraceae en México. Fase VI. 356 records from Morphologische Daten von Puffinus creatopus. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 23296 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 4 records from A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. 794 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 895 records from Geometridae de France métropolitaine. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1215 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1469 records from Marine eukaryotes Targeted loci environmental. 181 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 3 records from The Amphibians of the Mitaraka massif, French Guiana. 12 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 2704 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 298 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 2 records from Descriptions of two new Vietomartyria species (Lepidoptera, Micropterigidae) from China. 15360 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 71862 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1199 records from Oxygen minimal zone Targeted loci environmental. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 4 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 3939 records from Census of plant species in Pahou forest reserve. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 10719 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 7388 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 1785 records from 3Soil16S. 67 records from Relative abundance of ostracods in sediment core Sv09. 923 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 744 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 192 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 384 records from Saltern microbial community diversity. 93599 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 36 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 24 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 30 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 11 records from The types of skippers described by Shu-Iti Murayama (Lepidoptera: Hesperiidae). 20442 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 142 records from Size of planktic foraminifera at CTD station PS55/083-1. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 34523 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 246077 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 14 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 11032 records from Oregon Bee Atlas Survey Data: 2018. 9 records from Hybrizontinae (Hymenoptera, Ichneumonidae), a new subfamily for the fauna of Turkey. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 104 records from Birds Specimens of Akita Prefectural Museum. 1070 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 3 records from Rideriana amazonica gen. nov. and sp. nov. of Pentatomini (Heteroptera, Pentatomidae). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 3 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 101 records from Données naturalistes de LE GLOANEC Vincent. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 557 records from Corn bunting breeding distribution in Scotland. 7122 records from Whale catches in the Southern Ocean. 1 records from -- First- - description -- of- - the- - male- - of- - Dendrothrips karnyi (Thysanoptera, -- Thripidae) - from- - Iran. 405 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 3216 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 15 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 6 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 40793 records from Banded Iron Formation and Greenstone survey data. 38 records from Microzooplankton abundance and biomass at station TT045_19-3. 43 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 82 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 2 records from Description of Walkeriella miraculosa, gen. n. et sp. n. from South-East Peru (Lepidoptera: Hepialoidea: Hepialidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 797 records from Mycological collection of the National Museum. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 78 records from Herbarium BSG Hepaticopsida. 19 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 8301 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 71 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 1264 records from Grand Voyeux - Suivis scientifiques. 43 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 164 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 77 records from UWIZM Cnidarians. 226 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 272 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 167020 records from Tasmanian Museum and Art Gallery provider for OZCAM. 962 records from TTRS Mammals. 32 records from Review of genera of Sciomyzidae (Diptera: Acalyptratae) from China, with new records, synonyms, and notes on distribution. 11 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 15 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 534 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 45 records from Brown bear monitoring data from Deosai National Park. 862 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 97797 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1636 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2590 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT University Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 41 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 1 records from A new species of freshwater Chaetonotidae (Gastrotricha, Chaetonotida) from Obodska Cave (Montenegro) based on morphological and molecular characters. 89 records from Faunal assemblage of sediment core TR149-32. 61 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 1 records from A new genus and species of pigeon (Aves, Columbidae) from the Kingdom of Tonga, with an evaluation of hindlimb osteology of columbids from Oceania. 1 records from Cribrilinids (Bryozoa, Cheilostomata) associated with deep-water coral habitats at the Great Bahama Bank slope (NW Atlantic), with description of new taxa. 3 records from Two new scale insect species (Hemiptera: Coccomorpha: Acanthococcidae and Pseudococcidae) and a new country record from protected areas in Iran. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 6901 records from La familia Asclepiadaceae en México. 12 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 370 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 27 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 29 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 19 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 41 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 361 records from Données de VINCENT Alexis (SAPROX). 4 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 20709 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 89 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 53 records from Jumping plant-lice (Hemiptera: Psylloidea) of Afghanistan. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 63 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 26635 records from Plan de vertebrados de la Patagonia. 9 records from Tribe Myrmeleontini (Neuroptera: Planipennia: Myrmeleontidae) in Iran. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Description of a new water mite species of the genus Lebertia Neuman, 1880 (Acari, Hydrachnidae: Lebertiidae) from Russia. 4 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 40 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 10825 records from Census of species recorded during phytosociological surveys in Benin. 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 19569 records from Collection Pisces SMF. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41141 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 120716 records from Microbial biogeography of 925 geothermal springs in New Zealand. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 15 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 14426 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 21 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 2 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 16 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 150 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1641 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 2 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 224 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 165 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 370 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 159 records from Total foraminifera counts from multinet M31/3_MSN915. 925471 records from NatureServe Network Species Occurrence Data. 41676 records from Tagged Seal Location Data from SOGLOBEC. 3 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 11 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 333 records from Données naturalistes de Renaud PUISSAUVE. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 839 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 21 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1748 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1709 records from The Gibson spider collection. 52 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 4 records from A new species of Scinax Wagler (Hylidae: Scinaxini) from the tropical forests of Northeastern Brazil. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 460 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 34 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 12 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 16 records from Herbarium Senckenbergianum (FR) - Protista. 243 records from Colección de helechos de la FML. 66164 records from Florida Keys Reef Visual Census 1996. 3 records from Zoology in the Middle East. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 52646 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 2 records from Revision of the types of species of Alloxysta described by Cameron and Fergusson (Hymenoptera: Figitidae: Charipinae) and deposited in the Natural History Museum (London), including a key to the fauna of Great Britain. 11 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 4133 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 228695 records from Wild bees of Belgium. 164 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 20 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 95 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 5559 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 288 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 2 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 550 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 117 records from Nannofossil abundance of Hole 49-408. 1 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 304 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 17 records from Analyses of the recent components of sediment core PS1011-1. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9143 records from Royal British Columbia Museum Entomology Collection. 62 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 33 records from Dinoflagellate abundance of Hole 81-552. 31 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 35 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 2110 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 11 records from Eight new Lepadellidae (Rotifera, Monogononta) from the Congo bring to level endemism in Africa’s rotifers. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 6 records from Foraminifera abundance of Hole 58-442. 144 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3001 records from Colección Entomológica CDMB. 1046 records from NZCS Invertebrates New Collection After 1987. 10122 records from Uncultured eukaryotes Targeted Locus (Loci). 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 16931 records from Lepidoptera (Specimens NRM). 13 records from Coleção de Coleoptera da Universidade de Brasília. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 98 records from Warnowtal (Rostock). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 49 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 27728 records from Collection of saproxylic and xylobiont Beetles. 2747 records from Compost microbe establishment and growth in agricultural soils. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 202122 records from National Benthic Inventory. 56 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 16 records from Phenological Center - Fishes (Murmansk). 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 22534 records from Tachinid Recording Scheme - GB and Ireland records. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 5 records from The second species of the genus Gorochovius Xie, Zheng & Li, 2004 (Orthoptera: Phalangopsidae: Phaloriinae) discovered from China. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 25 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 4 records from Données naturalistes de Mikaël PAILLET. 10 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 1722 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 9756 records from Collection Trichoptera - SMF. 11433 records from Insectes Hétéroptères Mirides de France. 12 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 8 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 561 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 618 records from Pollen analysis of sediment core GeoB6518-1. 99 records from Planktic foraminifera abundance of Hole 27-262. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 27 records from Planktic foraminifera abundance of Hole 27-260. 129146 records from Arizona State University Hasbrouck Insect Collection. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 1 records from Megasybacodes brevitarsis, a new genus and species of Rhyparini (Coleoptera: Scarabaeidae: Aphodiinae) from Borneo. 236 records from Collection Strepsiptera SMF. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3353 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 33 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 26 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 24 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 4000 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 29 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 10 records from First records of the genus Spilopteron Townes (Hymenoptera: Ichneumonidae: Acaenitinae) from Vietnam, with descriptions of five new species. 620 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 87901 records from MDFRC macroinvertebrate survey. 1 records from Planktic foraminifera abundance of Hole 54-420A. 128 records from Inventaire des reptiles 2014. 8 records from A New Genus And Species Of Orsillinae (Heteroptera: Lygaeoidea: Lygaeidae) From Argentina. 40135 records from DIBA-Parc del Montnegre i el Corredor. 4761 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 223919 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 58 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 28994 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 8 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 141 records from Cepario de Microorganismos y Hongos Filamentosos de la Universidad del Valle. 7 records from Grundwasserlebensraum im Englischen Garten (München). 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 208 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 12 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 8218 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 753 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2939 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 61 records from Shrews of Poland. 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 1 records from A new African species of Stenichnodes (Coleoptera: Staphylinidae: Scydmaeninae). 9 records from Nannofossil abundance of Hole 2-11. 46464 records from Données naturalistes de Pascal Dupont. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 2167 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 348 records from Bird specimens of Bihoro Museum. 166 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 147 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 15 records from Nannofossil abundance of Hole 6-48B. 2 records from Wie viel Natur gibt es im Park?. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 29876 records from European Moth Nights. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 3 records from A new species of Bicoxidens Attems, 1928 (Diplopoda, Spirostreptida, Spirostreptidae) from northern Zimbabwe. 1096 records from Zootaxa. 6779 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A review of South Korean Alloplasta Förster (Hymenoptera: Ichneumonidae: Banchinae) with description of a new species. 10150 records from NBMB Herps. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 342 records from Foraminifera distribution of sediment core KS310. 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 9542 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 94 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 1036 records from BUND - Dassower See (Lübeck/Dassow). 57203 records from Données naturalistes de Monsieur François FOURNIER. 393 records from NHMO DNA Bank Other groups collection. 1 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 69 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 54298 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 3 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 23 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 15 records from Three new species of the genus Rhyzobius Stephens, 1829 from New Guinea (Coleoptera: Coccinellidae: Coccidulini). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 7 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 147 records from Données de la naturaliste Laurence Beauchamp. 240 records from Knechtweide (Kohlfurth). 4981 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 92 records from Collections ichtyologiques et herpétologiques (BOUM). 1405 records from MCP-Mamiferos - Coleção de Mamíferos. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15040 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 68 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 89 records from Meniscus Midges (Dixidae) of Ireland. 2 records from A new species of the genus Tagasta Bolivar, 1905 (Orthoptera: Pyrgomorphidae) from India. 20 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1707 records from Occurrence database of native plants and animals of south-central Chile. 80 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 281625 records from ARABEL - Arachnologia Belgica. 124513 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 1 records from Rediscovered syntypes of Procrangonyx japonicus, with nomenclatural consideration of some crangonyctoidean subterranean amphipods (Crustacea: Amphipoda: Allocrangonyctidae, Niphargidae, Pseudocrangonyctidae). 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 62791 records from MLZ Bird Collection (Arctos). 449 records from Artsprosjekt Pyrenomycetes. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 75152 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 10 records from Données bibliographiques ASFRA. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 5061 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 3400 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 7718 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 390 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 4585 records from Marine bacteria Targeted Locus (Loci). 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 280 records from Atlantic Forestry Centre Insect Reference Collection. 2 records from Review of the species of Anastatus (Hymenoptera: Eupelmidae) known from China, with description of two new species with brachypterous females. 11873 records from Midden-Limburg Fish Ponds Survey. 2743 records from marine sediment metagenome Raw sequence reads. 96 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 76064 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 7 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 3 records from Review of Campsicnemus species from the Atlantic Ocean Islands (Diptera: Dolichopodidae). 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 16 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 2352 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 45835 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 37 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 29986 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 552 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 1270 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 127 records from Сypripedium guttatum Sw. in the Komi republic. 2116 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 11 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A new tyrannosaurine (Theropoda: Tyrannosauridae) from the Campanian Foremost Formation of Alberta, Canada, provides insight into the evolution and biogeography of tyrannosaurids. 27 records from The first species of Cotithene Voss (Coleoptera: Curculionidae: Curculioninae) from Amazonian Brazil, with notes on its role as a pollinator of Evodianthus funifer (Poit.) Lindm. (Cyclanthaceae). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 146 records from Abundance of birds in the Lena Delta Region. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 54 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 247 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 31 records from Planktic foraminifera counts of sediment core V19-21. 67 records from artsprosjektet_48-13_monomyx. 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 25138 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 5250 records from Colección Ornitológica de la Universidad del Valle. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 279484 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 8 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 46693 records from Botanical Museum, Copenhagen, Mycology Herbarium. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 16767 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 90 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 6 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 95889 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 216890 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 92 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 10 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 5 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 152 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 52 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 7735 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 612 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 7627 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 2 records from A new record of the genus Orientalicesa Koçak & Kemal, 2010 (Hymenoptera: Vespidae: Eumeninae) from Vietnam. 6 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 248 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10184 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 16505 records from Database for alien invasive plants occurrences in Germany. 62 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8969 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 15 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 407 records from Strathclyde badger sett surveys 1996-2000. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 22173 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 64 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 338 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 1 records from First record of Undabracon Quicke, 1986 (Hymenoptera: Braconidae, Braconinae) from the Indian subcontinent with the description of a new species. 12385 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 15 records from Revision of the terrestrial isopods of the subgenus Hemilepistus (Desertellio) Verhoeff, 1930 (Isopoda: Oniscidea). 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 2863 records from Inventaire des Mollusques Sphaeriidae de France. 17073 records from données aranéologiques de CORNIC Jean-François. 359 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from A new species of the genus Sovia Evans, 1949 from South Central Yunnan, China (Lepidoptera, Hesperiidae). 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 66 records from Planktic foraminifera abundance of Hole 22-212. 2 records from Nannofossil abundance of Hole 4-26A. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 55 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 366 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 567 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 245 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 114 records from Measurements of elephant tusk trophies taken in Botswana 1999. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 4 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 36 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 1 records from Two new species of the genus Odochilus Harold, 1877 (Coleoptera: Scarabaeidae Aphodiinae: Odochilini). 11 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 6652 records from Inventory of plant species through Benin (West Africa). 6 records from A review of the genus Tuberaleyrodes Takahashi (Hemiptera: Aleyrodidae) with description of five new species from Brunei, Hong Kong and Malaysia. 3 records from The bee genus Caenaugochlora (Hymenoptera, Apoidea) and its constituent subgenera, with new species of Caenaugochlora s. str. from Ecuador. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 3 records from One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China. 17 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 4 records from A new species of the Neotropical genus Beebeomyia (Diptera: Richardiidae) with observations of its biology on Dieffenbachia oerstedii (Araceae). 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 2 records from Description of a new species of the genus Tophoderes Dejean (Coleoptera: Anthribidae) from east Madagascar, with images of all Madagascan species of the genus. 4 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 6 records from A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy). 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 61 records from Nemertini - SMF. 5 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 2 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 53 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 18 records from Descriptions of two new species of Rhopalovalva Kuznetzov, 1964 (Lepidoptera: Tortricidae) from China. 1 records from A new species of frog (genus Eleutherodactylus) from a cloud forest in Western Colombia. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 993 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 110784 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 2 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 26 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 337008 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 640 records from Annales de la Société Linnéenne de Maine-et-Loire. 6 records from The Afrotropical braconine genus Dioxybracon Granger with descriptions of four new species and new generic synonymy. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 39 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 51 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 330 records from Fossil Specimens of Komatsu City Museum. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 22 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 5 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 3320 records from BioGIS - Mammals - SPNI. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 1 records from A new species of freshwater crab of the genus Badistemon Yeo & Ng, 2007 (Decapoda: Brachyura: Potamidae: Potamiscinae) from Manipur State, India with the reassignment of Potamiscus pealianus (Wood-mason, 1871). 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 3417 records from MEXU/Flora de Oaxaca. 37606 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2 records from The Genus Episynlestes Kennedy (Odonata: Synlestidae). 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 62 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 33 records from Crickets of the subfamily Itarinae Shiraki, 1930 (Orthoptera: Gryllidae) from China with description of a new species and distribution and critical notes on other species. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2760 records from Données naturalistes d'Alain BERLY. 105925 records from Herps Specimens. 39092 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 12724 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 231973 records from Données de la flore d’Alsace (SBA). 5 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 24880 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 384 records from Nannofossil abundance of Hole 17-167. 270 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 289 records from bmhs_butterfly_collection. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 172 records from checklist-of-birds-of-zomba-mountain. 108775 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1390869 records from Flore Franco-Belge. 62238 records from EAC - Herbário Prisco Bezerra. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from Hoplophthiracarus sidorchukae sp. nov. (Acari, Oribatida, Phthiracaridae) from the North Island, New Zealand. 1541 records from Leif Richardson Vermont Bee Specimens. 44 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 7062 records from Collection Crustacea - ZMB. 645 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 9 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 25 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 10 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 10 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2660 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 109 records from Planktic foraminifera abundance of Hole 18-181. 2 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 401 records from Planktic foraminifera distribution of sediment core SU81-07. 1632 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 86676 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 449635 records from Herbarium of Taiwan Forestry Research Institute. 25 records from Pyura gangelion and Pyura beta sp. nov. (Ascidiacea: Pyuridae): an exotic and a new tunicate from the West Atlantic. 23 records from Ackerrain Plönhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 243 records from Malawi-Histeridae-Biodiversity-Data. 426 records from Planktic foraminifera abundance of Hole 7-64. 29 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 85 records from (Fig. 4) Nannofossil abundance of Cretaceous profile Pré-Guittard, SE France. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 12 records from Rotundocoris, a new apterous genus of Carventinae from China (Heteroptera: Aradidae). 199157 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 5520 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4644 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4046 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 7 records from Four new species of Mileewini leafhoppers (Hemiptera: Cicadellidae: Mileewinae) from China, with a checklist to Chinese species. 255 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 2225 records from Données naturalistes d'Anaïs MAS. 2430 records from Microbial community diversity in Arctic marine sediments and Planktonic microbial. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 12 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 8144 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Abundance of benthos infauna at station GIK23065-1. 1205 records from uncultured eukaryote Raw sequence reads. 22661 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 5 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4 records from Planktic foraminifera abundance of Hole 17-166. 283 records from Flux data of NU2_trap (Table A1). 10 records from Revision of the bee genus Chlerogella (Hymenoptera, Halictidae), Part I: Central American species. 2842833 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 7 records from New data on cockroaches of the subfamily Epilamprinae (Dictyoptera: Blaberidae) from India and Sri Lanka, with descriptions of new species and the genital complex of Aptera fusca (Thunberg, 1784). 5346 records from Sediment metagenome. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15242 records from Anymals+plants - Citizen Science Data. 1229 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 71095 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 1689 records from CNAN/Scorpiones. 94 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 5 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 7 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 1054 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 694 records from données arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 4 records from Nannofossil abundance of Hole 3-22. 3 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 6 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 2 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 17 records from Review of Chinese species of the Oxylipeurus - complex (Phthiraptera: Philopteridae), with descriptions of two new genera and five new species. 57504 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 1 records from Porifera ZMK. 2 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 5 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 46 records from Revision of the genus Tmesiphorus LeConte, 1849 (Coleoptera: Staphylinidae: Pselaphinae) from Japan. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 25899 records from JCT AVH data. 33 records from Planktic foraminifera counts of sediment core V28-128. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 21703 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 237 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Bioacoustics review of Anatolian species of the predatory bush-cricket genus Saga (Orthoptera: Tettigoniidae: Saginae) with the description of a new species. 23 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 433 records from Amphibiens de Guyane. 134 records from Nannofossil abundance of Hole 7-62A. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 11 records from Nannofossil abundance of Hole 9-82. 10 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from Planktic foraminifera abundance of Hole 20-200A. 575 records from Nannofossil abundance of Hole 75-530A. 3 records from One new species and new record of the leafhopper genus Watara Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 6 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78572 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 6 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3495 records from Dorset SW Pilot species dataset. 1922 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 7 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 2 records from Review of the Stenoscelidea complex and key to the known genera of Stenoscelideini (Hemiptera: Heteroptera: Coreidae). 35 records from Inventaire et suivi de la faune écrasée. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 17 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 3003 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 393 records from Analysis of plasmidome of high-altitude lakes from the Andean Puna. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from Loricifera - SMF. 3 records from New records and their associated DNA barcodes of the butterfly family Hesperiidae in Tibet, China. 191 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 23 records from Taxonomic Accounts With Notes On Spatial Diversity And Relative Abundance Pattern Of Horseflies (Diptera: Tabanidae) From Sonamukhi Protected Forest Area Of West Bengal, India. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 66 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 207 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 69 records from BIRDRACE Pfeifenten. 69 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 23449 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 4607 records from Données de type contact en Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351728 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 1767 records from Canadian Museum of Nature Palynology Collection. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 655 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 8 records from Revision of Afrotropical species of the Philonthus peripateticus species group (Coleoptera: Staphylinidae: Philonthina). 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 978 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 15 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 55 records from Galls on Beech Trees in Hainich, 2008. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 181825 records from Carnet B Lorraine. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 7 records from A review of the Oriental leafhopper genera Thampoa Mahmood and Guheswaria Thapa (Hemiptera: Cicadellidae: Typhlocybinae). 4080 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 126 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 5248 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 66395 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 12074 records from Weevil and Bark Beetle records via iRecord. 18 records from Review of the leafhopper genus Alnetoidia Dlabola (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 4 records from New species of Langona Simon, 1901 and Neaetha Simon, 1884 (Araneae Salticidae) from Thailand. 982 records from Diatom assamblage in samples from sediment trap OG4. 2132 records from DAR AVH data. 170543 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 8 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 2 records from Multiple original spellings, living authors and the Code: The case of Malachius raniansis Mawlood, Hammamurad & Abdulla, 2017 (Coleoptera: Melyridae). 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 859 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 3178 records from Newfoundland sediment pyrosequencing. 4 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 5 records from Systematic account of new Porifera (Demospongiae) records from the oceanic Island of Madeira (NE Atlantic). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 37 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2156 records from Thrips (Thysanoptera) in Norway. 4065 records from Microbial community in permeable intertidal sediment. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 362 records from Mammalian Specimens of the Yamagata Prefectural Museum. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 22 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1764 records from Arachnida of Costa Rica (INBio). 675 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 3148 records from Ross A. Layberry, Collection. 2 records from Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 92 records from Microfossil abundance of Hole 50-416A. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 15 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 2 records from A new Palnia STEBNICKA, 1985 species from Oriental region (Coleoptera, Scarabaeidae, Aulonocneminae). 4 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 4 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 448 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 7346 records from Colecção Entomológica do Museu de História Natural de Maputo. 11 records from Three new species of Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) from Taiwan, China, with an updated key for L. shibatai Sawada-group. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 722 records from Heritage Trees of Ireland. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 2146 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 140 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 58925 records from Isopoda (Interim dataset). 1 records from A new epigean species of the genus Anelpistina (Insecta: Zygentoma: Nicoletiidae) from Sierra de El Abra, Taninul, Mexico. 5 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 89 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 1109 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 173049 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 474 records from Données du/de la naturaliste VINCENT Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from New species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae: Meconematini) from Sichuan, China. 3176 records from Algae collection, Oslo (O) UiO. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 6 records from Nannofossil abundance of Hole 6-49. 29 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 5061 records from Metagenome from mudbank Area,Alappuzha Kerala India. 5 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 55 records from Planktic foraminifera abundance of Hole 16-161. 29288 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 956 records from Guinea-Bissau Herpetological Collection - IICT. 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 967 records from Inventaire des Odonates. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 906 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 3 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 34 records from Planktic foraminifera counts of sediment core V27-47. 312 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 1 records from On the rare Neotropical genus Ophionthus Bernhauer (Coleoptera: Staphylinidae: Staphylininae): redescription of the type species and description of a new species. 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1460 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 368 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 102 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 1 records from On the Chilopoda from Turkey. 143 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 84 records from The Stephanidae (Hymenoptera) of Mexico, with description of six new species and key to western Foenatopus Smith. 4 records from First record of the genus Raunolina (Hemiptera: Fulgoroidea: Caliscelidae) from tropical Africa with description of two new species from Sudan and Saudi Arabia. 60 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 1 records from A new garden eel, Heteroconger fugax (Congridae: Heterocongrinae), from the northwestern Pacific Ocean. 278 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 231 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 2 records from Bracon planitibiae sp. nov. (Hymenoptera: Braconidae), a new parasitoid of Asian longhorned beetle (Anoplophora glabripennis). 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 73579 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 143 records from Toxicity of copper to three Macquarie Island marine gastropods 2013/15. 999 records from Bird collection Natuurmuseum Brabant, Tilburg. 77 records from Benthic foraminifera abundance of Hole 42-372. 1423 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 469132 records from Natural England Marine Monitoring surveys. 705 records from Range table from benthic foraminifers in ODP Hole 139-857A. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 126 records from Foraminifera species abundances from tow TT011_10-MOC71. 58 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 4 records from Alucitidae (Lepidoptera) of Korea: Description of a new species and records of two previously unrecorded species. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 425 records from Collection de C.C.H. Jongkind aux Monts Nimba. 3 records from A new Brazilian species of Harpasus Mulsant (Coleoptera, Coccinellidae, Chilocorinae), a predator of Tinocallis kahawaluokalani (Kirkaldy) (Hemiptera, Aphididae). 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 4 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 10138 records from The Vascular Plants Collection of the University of Goettingen. 29555 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2103 records from Flora vascular acuática de la cuenca del Río Tamesí. 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 8 records from New data on brown lacewing genus Wesmaelius Krüger, 1922 from China (Neuroptera, Hemerobiidae), with a key to Chinese species. 14 records from Type locality records of Polycystididae species in the world. 5326 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1122 records from Données naturalistes de Stéphane ORIO. 190 records from Collection Echinodermata - ZMB. 364 records from Inventario herpetofaunístico del noroeste de Hidalgo. 32256 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 1 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 21 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 166 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 3 records from Taxonomic review of Chin-wen Chen’s species described in the genus Smicromyrme (Hymenoptera: Mutillidae). 2316 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from First record of Caliscelis (Caliscelis) bonellii (L, 1807) (Hemiptera: Fulgoromorpha: Caliscelidae) from Turkey, with redescription of the species. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 3990 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 106 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 17 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 374 records from Medicinal potential of African plants (Togo). 542 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 5 records from Notes on types of Australian Chartocerus Motschulsky (Hymenoptera: Signiphoridae). 9786 records from The Suguru Igarashi Insect Collection (Lepidoptera: Lycaenidae) of The University Museum, The University of Tokyo. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 3 records from Description of a new species of Andaeschna (Odonata: Aeshnidae) from the Western Colombian Andes. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1191 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 146 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 3 records from A new flower bug of the genus Montandoniola (Hemiptera: Heteroptera: Anthocoridae), a predator of gall-forming thrips on black pepper in southern India. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 172422 records from Hymenoptera specimen database of Kyushu University. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 11 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 728405 records from Finnish Floristic Database (Literature Sources). 151 records from The Myriapoda Collection of the National Museum of Nature and Science. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 402 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 71639 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1719 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 232 records from Inventaire avifaune. 9329001 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 117 records from Nannofossil abundance of Hole 41-366A. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 3 records from А new species of Alona Baird, 1843 (Cladocera: Chydoridae) from the ancient Lake Ohrid. 28 records from Bohemannia auriciliella (Nepticulidae) specimen data. 29 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 74 records from Nannofossil abundance of Hole 39-359. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 28 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 113 records from Nannofossil abundance of Hole 49-412. 24 records from Abundance of benthos infauna at station PS1240-1. 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 5 records from New records of biting midges (Diptera: Ceratopogonidae) from the United Arab Emirates, with a description of a new species. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 25 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 31 records from New records of chalcidid (Hymenoptera: Chalcididae) pupal parasitoids from India. 22 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 75 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 17 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 1834 records from Coleoptera Collection. 1 records from Extended diagnosis of the type species of Pseudogonatodes Ruthven 1915 (Gekkota Sphaerodactylidae). 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 415 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1260 records from Kangawalla Bird Sightings. 228 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 2128 records from Occurrence (present/absence) and abundance of zooplankton in Murchison Bay, Lake Victoria. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 2997 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 42 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 8 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 213 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 4 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 671 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 37651 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 2 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 53961 records from Long-Term Monitoring Network Vegetation Quadrats. 18 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 517 records from Collection Crustacea ZMG. 2 records from Revision of Chinese mainland Hybovalgus Kolbe, 1904, with description of a new species, and Excisivalgus Endrödi, 1952 reduced to synonymy with Hybovalgus (Coleoptera: Scarabaeidae). 83 records from Naturpark Kottenforst-Ville 16.6.09. 1170 records from Araneae Collection. 5 records from Description of two females of Leptagrion Selys (Odonata: Coenagrionidae). 244 records from Planktic foraminifera abundance of Hole 15-154A. 3 records from First record of a native Atomaria S, 1829 (Coleoptera: Cryptophagidae) from the Neotropical Region. 4 records from Description of Coladenia simianensis sp. nov. (Lepidoptera: Hesperiidae) from China, with an annotated checklist of the genus Coladenia Moore, 1881. 1 records from Inventaire des sangsues - détermination des échantillons de l'enquête participative - Subvention UMS Patrinat. 114823 records from Marine metagenomes from the bioGEOTRACES project. 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 176 records from Recursos hidrobiológicos de Caño Cristales, La Macarena, Meta. 288115 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 23 records from TBW-Schafberg. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 4268 records from Observations et collection de Coléoptères d'Alain Sadorge. 25 records from Total foraminifera counts of multinet M42/3_MSN1368. 7 records from Notes on the spider genus Segestria Latreille, 1804 (Araneae: Segestriidae) in the East Palaearctic with description of three new species. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 19 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 161 records from Insect specimens of Mie Prefectural Museum. 728 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 131 records from Unser Schulhof - eine Apotheke. 1 records from Chance, luck and a fortunate finding: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes: Xenodontinae), from the Brazilian Pantanal wetlands. 2972 records from B herbarium - Botanischer Garten und Botanisches Museum Berlin-Dahlem Herbarium - Herbário Virtual REFLORA. 1688 records from Southern Maine Community College Gulf of Maine Invertebrate Data. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 37 records from Berlin - Treptower Park / Karpfenteich. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 247577 records from Bacterial diversity and community composition in grassland and forest soils of the German Biodiversity Exploratories. 8080 records from El género Bursera en México. Parte II. 69559 records from HUFU herbarium - Universidade Federal de Uberlândia - Herbário Virtual REFLORA. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 458 records from PSUZC-Mammal Collection. 3 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 4 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 2 records from A new genus and species of micropterous Oriental Aradidae (Hemiptera, Heteroptera, Aradidae). 371 records from GCP_2017_12_18. 264 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 2 records from Description of a new species of Chrysina Kirby (Coleoptera: Scarabaeidae: Rutelinae) from the Sierra Azul, Oaxaca, Mexico, a new synonymy, and notes on Chrysina species found in the Sierra Azul. 2657 records from Aves del Distrito de Páramos en los departamentos de Nariño-Putumayo. 26 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 1247 records from Antarctic Jellyfish. 18 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 71 records from Données naturalistes d'Audrey SAVOURE-SOUBELET. 594867 records from National Trust Species Records. 6756 records from Diversité floristique des espèces menacées prioritaires du Bénin (Afrique de l'Ouest).. 254 records from Pukkellaks i Norge 2017. 20435 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Collembola). 74 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 14 records from Revision of the genus Alkindus Distant (Hemiptera: Heteroptera: Thyreocoridae: Corimelaeninae). 80 records from Données naturalistes d'Emmanuel ICARDO. 4963 records from NHM, Heteroptera. 1 records from A new species of Mastostethus (Coleoptera: Chrysomeloidea: Megalopodidae) from Chiapas, Mexico. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 22 records from Asian cave-adapted diplurans, with the description of two new genera and four new species (Arthropoda, Hexapoda, Entognatha). 33 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 1367503 records from Australian Museum provider for OZCAM. 5221 records from Acoustic monitoring data of anuran species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 6 records from Taxonomy of coccids (Hemiptera: Coccidae: Coccus L.) associated with Crematogaster ants (Hymenoptera: Formicidae) in the stems of Macaranga plants (Euphorbiaceae) in Southeast Asia. 141 records from Revision of the South African endemic bee genus Redivivoides Michener, 1981 (Hymenoptera: Apoidea: Melittidae). 1 records from 5. Wiener Gemeindebezirk. 32724470 records from Observation.org, Nature data from around the World. 1 records from Record of genus Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae; Copiphorini) and description of one new species from India. 14 records from Description of the female of Labena madoricola González-Moreno & Bordera, 2015 (Hymenoptera, Ichneumonidae, Labeninae), with new records of Labena species from Mexico. 6 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 17 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 7405 records from Mammal records for Dumfries and Galloway. 471 records from Phytoplankton data collected from a diurnal station in Sevastopol Bay (Black Sea) during 1952. 4 records from African Spilogona Schnabl: morphology of the male terminalia and description of a new species (Diptera: Muscidae). 90 records from Herbario MAIA, colección de Ericas del INIA-CIFOR. 58 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 97 records from Streuobstwiese Stedar 2008. 4059 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 2008 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 30987 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 43183 records from Canadian Museum of Nature Fish Collection. 60057 records from JPB - Herbário Lauro Pires Xavier. 136 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 148 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 6 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 5 records from A new species of Uvarus Guignot, 1939 (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) from Florida, USA. 1198 records from 2019_MJIM_IN. 2 records from Entomologische Nachrichten und Berichte. 196 records from Revision of Netomocera Bouček (Hymenoptera: Chalcidoidea: Pteromalidae), excluding the Oriental species. 149 records from Données naturalistes de l'inventaire malacologique pour l’élaboration de deux dossiers de création de Réserve naturelle régionale (RNR) - Sites des Terrils n° 11 et 12 du Bois des Dames (Bruay-la-Buissière) et Ex-sablière de Chocques. 908 records from Bats of Poland. 127 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 11 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, >150 µm. 88548 records from Field Museum of Natural History (Botany) Bryophyte Collection. 2 records from Late postnaupliar development of the freshwater copepods Lovenula falicifera and Metadiaptomus colonialis (Calanoida: Diaptomidae) from South Africa. 11 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-083BX. 26489 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 89275 records fro
Keywords: GBIF; biodiversity; species occurrences